Expired platelet concentrate as a source of human platelet lysate for xenogeneic-free culture of human dermal fibroblasts - Muhammad Najib Fathi Hassan,; Yap, Zheng Yie; Tang, Yee Loong; Ng, Min Hwei; Law, Jia Xian (Penerbit Universiti Kebangsaan Malaysia, 2021)
Dermal fibroblasts have been used clinically to promote wound healing and to reduce wrinkles. Most of the time, fetal bovine serum (FBS) is used for the expansion of fibroblasts. In addition, chemically defined medium can also be used for fibroblast expansion. Nonetheless, both FBS and chemically defined medium are not ideal to culture cells that will be used clinically as FBS has the risk of pathogen transmission and induction of xenogeneic immune response whilst chemically defined medium is extremely expensive. In this study, we examine the potential of using human platelet lysate (hPL) prepared from expired platelet concentrates to culture human dermal fibroblasts. For the experiments, fibroblasts were cultured with 5 and 10% hPL, with 10% FBS as the control group to compare the cell morphology, viability, growth rate, extracellular matrix gene expression and wound healing. Results showed that fibroblasts cultured with hPL were more elongated and smaller in size. The cell viability was higher than 90% for all groups. Expansion with 10% hPL significantly shorten the population doubling time compared to the 5% hPL and 10% FBS groups. However, fibroblasts cultured with hPL have lower expression of type I collagen, type III collagen and fibronection as well as slower wound closure. In summary, hPL has the potential to be used as a serum substitute for FBS to expand fibroblasts as it significantly increases the cell proliferation. However, further studies are required to determine if the changes in the ECM gene expression and migration of the hPL-expanded fibroblasts will affect the efficacy of the cells in promoting in vivo wound healing.